Increased Efficacy and Tolerability of Pegloticase in Patients With Uncontrolled Gout Co-Treated With Methotrexate: A Retrospective Study - John A. Albert; Tony Hosey; Brian LaMoreaux (Rheumatology and Therapy, 2020)
Abstract Introduction Gout is a painful inflammatory condition caused by chronically elevated serum uric acid levels (sUA). When standard urate-lowering therapies fail/are not tolerated, uncontrolled gout (elevated sUA, subcutaneous tophi, chronic gouty arthritis, frequent flares) can occur. Pegloticase, a recombinant uricase, converts uric acid to allantoin, a readily excreted molecule. Responder rate in trials was 42%, limited by anti-drug antibody (ADA) development. Immunomodulators attenuate ADA formation and case reports suggest immunomodulation increases pegloticase responder rates. The current study retrospectively examined responder rate in patients undergoing methotrexate/pegloticase co-therapy. Methods Patients who underwent methotrexate/pegloticase co-treatment at a single rheumatology practice were included. Demographics, clinical, treatment, and safety parameters were collected. The primary outcome was the proportion of responders (≥ 12 biweekly pegloticase infusions, sUA < 6 mg/dl just prior to infusion 12). Results Ten patients (nine men, 52.3 ± 13.5 years) with uncontrolled tophaceous gout (erosive damage, ulcerative tophi, frequent flares, gout-related hospitalizations) were included. Patients had failed allopurinol (100–300 mg) or febuxostat (40 mg) therapy (doses not increased because of intolerance, kidney concerns, noncompliance, or rapid tophi resolution requirement). Baseline sUA was 9.42 ± 2.05 mg/dl. Along with standard pre-infusion prophylaxis, nine patients received subcutaneous methotrexate (25 mg/week) initiated 14–35 days before pegloticase and one patient received oral methotrexate (12.5 mg/week) initiated 14 days after pegloticase. Eight patients (80%) were responders, receiving 15.5 ± 3.8 infusions (range, 12–21) over 31.8 ± 9.5 weeks. One patient had efficacy loss with mild infusion reaction during infusion 4 and one patient was lost to follow-up after infusion 5. One patient reported one gout flare. No new safety concerns emerged. Conclusions Methotrexate/pegloticase co-therapy resulted in a higher responder rate than the established 42% with pegloticase alone. Therefore, methotrexate/pegloticase co-therapy may safely allow more patients to benefit from a full treatment course, likely through ADA attenuation.